Best Answer

From the question, I think this is the equation: (1/a) - (5/3a) = 1/3 I'll take this slow. First, multiply both sides of the equation by 'a': (1) - (5/3) = a/3 Now multiply both sides by 3: (3) - (5) = a a = -2

Q: How do you find a in the equation 1 over a - 5 over 3a equals 1 over 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is an equation because: a = 6

3.5

a+7/3 = 6 Multiply all terms by 3:- 3a+7 =18 3a = 18-7 3a = 11 a = 3 and 2/3

It is, in fact, an identity - which is an equation which is true for all values of the variable.

It's a linear equation in ' a '.When you see one of these, it often happens that curiosity overtakes you, and you begin to wonder about the numerical value of ' a ' that makes the equation true. Let's find out:3a - 7a + 12 = 323a - 7a = 20-4a = 20a = 20 / (-4) = -5The equation is true if ( a = -5 ).

Related questions

An equation.

It is an equation because: a = 6

It's a simple linear equation with 'a' as the variable.Here's how to find the solution:3a + 2 = a - 6Subtract '2' from each side of the equation:3a = a - 8Subtract 'a' from each side:2a = -8Divide each side by '2' :a = -4

yes, one in which a = 6

3.5

a+7/3 = 6 Multiply all terms by 3:- 3a+7 =18 3a = 18-7 3a = 11 a = 3 and 2/3

It is, in fact, an identity - which is an equation which is true for all values of the variable.

It's a linear equation in ' a '.When you see one of these, it often happens that curiosity overtakes you, and you begin to wonder about the numerical value of ' a ' that makes the equation true. Let's find out:3a - 7a + 12 = 323a - 7a = 20-4a = 20a = 20 / (-4) = -5The equation is true if ( a = -5 ).

a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100

3a-1=11 Now, you need to keep the equation balanced so whatever you do to one ide of the equation, you MUST do to the other. So the first step is to add 1 to each side of the equation (the equals sign), so we end up with numbers only on one side, and letters only on the other side (or multiples of letters, in this case 3 lots of A...).... 3a-1 = 11 +1 +1 which gives us... 3a+0 =12 or just 3a = 12 Now divide both sides of the equation by 3 to work out what one lot of 'a' is instead of three.... 3a = 12 ÷3 ÷3 a = 4

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.

No. 3a 12 plus a 6 is not a solution Of an equation.